2020
DOI: 10.3390/app10082718
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Accuracy of Static Guided Implant Surgery Measured by Optical Scan: Examining the Impact of Operator Experience

Abstract: Studies examining the effect of operator experience on the accuracy of static guided implant surgery have used postoperative computed tomography (CT) images to measure the error, with inconsistent results. The purpose of this study was to try to clarify this issue by using a measurement method based on the postoperative optical scan. Thirty dentists were divided into an experienced group and an inexperienced group. On a partially edentulous mandibular model in the manikin head, each dentist placed three implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
(49 reference statements)
2
9
0
Order By: Relevance
“…Many studies have reported the use of various software programs for 3D analysis [7,[22][23][24]. 3D analysis is sometimes applied to evaluate the processing precision of CAM as the surgical static guide for implant surgery and for the fixed and removable dental prosthesis fabricated by 3D printing or milling [1,12,13,26,27]; however, many studies have applied 3D analysis to evaluate the accuracy of 3D scanners [1,4,10,11]. The four software programs used in this study were used as evaluation tools for the accuracy of the 3D scanner in previous studies [2,6,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported the use of various software programs for 3D analysis [7,[22][23][24]. 3D analysis is sometimes applied to evaluate the processing precision of CAM as the surgical static guide for implant surgery and for the fixed and removable dental prosthesis fabricated by 3D printing or milling [1,12,13,26,27]; however, many studies have applied 3D analysis to evaluate the accuracy of 3D scanners [1,4,10,11]. The four software programs used in this study were used as evaluation tools for the accuracy of the 3D scanner in previous studies [2,6,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…A 3D analysis is possible only in specific analysis software programs, and analysis software programs released by various manufacturers are used [22][23][24][25]. In 3D analysis, the CAD reference model (CRM) and CAD test models (CTMs) are first aligned and 3D comparison is then performed, which is a general 3D analysis process (Figure 1) [26][27][28]. In the alignment process, the approximate positions of CRM and CTMs are initially aligned, followed by optimal alignment (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Two in vitro studies using surgical templates showed significantly greater deviations by non-experienced users [ 35 , 36 ]. However, in a similar setting to that of the present study, the subject’s experience was not demonstrated to be a critical factor in achieving the accuracy of implant position [ 37 ]. This lack of consistency could be explained by the design of the guide.…”
Section: Discussionmentioning
confidence: 92%
“…The influence of clinicians’ surgical experience on the accuracy of DGT-guided implantation is a research hotspot because it almost determines whether novice clinicians can be free to use DGTs for implantation. Lin et al [ 39 ] showed that when the tooth-supported guide template was used in a well-controlled environment, the surgical experience was not the key factor affecting the implant accuracy. Some scholars [ 37 ] studied the influence of surgical experience on the accuracy of the half-guided and the mucosa-supported guide templates and reached the same conclusion.…”
Section: Discussionmentioning
confidence: 99%